IMPACT OF FERTILITY PRESERVATION IN GYNECOLOGICAL MALIGNANCIES: ASSESSING INFERTILITY, PREGNANCY OUTCOMES, QUALITY OF LIFE, AND DECISION REGRET FOLLOWING FERTILITY-SPARING SURGERY. - Albayrak, Nazli; Gungor, Mete (ELSEVIER SCIENCE INC, 2023)
79th Scientific Congress of the American-Society-for-Reproductive-Medicine (ASRM), New Orleans, LA, OCT 14-18, 2023